2016
DOI: 10.3109/1354750x.2016.1171900
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic patterns associated to QTc interval in shiftworkers: an explorative analysis

Abstract: Objectives: 1H NMR-metabolomic approach was used to investigate QTc interval correlation with plasma metabolic profiles in shiftworkers. Methods: Socio-demographic data, electrocardiographic QTc interval and plasma metabolic profiles from 32 male shiftworkers, were correlated by multivariate regression analysis. Results: We found a positive correlation between QTc interval values, body mass index, glycemia and lactate level and a negative correlation between QTc interval and both pyroglutamate and 3-hydroxybut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…Nor did we observe in TTNtv carriers an alteration in urinary N-terminal titin fragments previously shown to be a negative prognostic indicator in HF [28]. We were unable to demonstrate any statistically significant correlations between metabolomic biomarkers and AECG; however, metabolomics has previously shown that kynurenine pathway is associated with mental stress-induced LVSD and ketone bodies (acetate and beta hydroxybutyrate) with QTc in shift workers [29,30]. We were, however, able to show an ability to not only discriminate between healthy participants and HF patients using PPSG and EDA, but also identify the presence of mental stress with a high degree of accuracy.…”
Section: Discussioncontrasting
confidence: 71%
“…Nor did we observe in TTNtv carriers an alteration in urinary N-terminal titin fragments previously shown to be a negative prognostic indicator in HF [28]. We were unable to demonstrate any statistically significant correlations between metabolomic biomarkers and AECG; however, metabolomics has previously shown that kynurenine pathway is associated with mental stress-induced LVSD and ketone bodies (acetate and beta hydroxybutyrate) with QTc in shift workers [29,30]. We were, however, able to show an ability to not only discriminate between healthy participants and HF patients using PPSG and EDA, but also identify the presence of mental stress with a high degree of accuracy.…”
Section: Discussioncontrasting
confidence: 71%
“…As work-related stress has been linked to CVD risk [1,2,3], monitoring QT-related parameters (QTc, QTi, QT variability, QT dispersion) might be useful to prevent a major cause of death, disability, and loss of productivity. By reaching a large fraction of the general population, the periodical occupational health surveillance [17,20,21,30,40] is a point of intervention: in fact, it might allow more effective preventive action through detecting early changes in biological parameters in otherwise healthy subjects. This aspect might have important public health implications, by reducing the direct and indirect costs of cardiovascular disease related to work-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace factors, such as shiftwork in irregular and unpredictable working hours, can induce changes in the length of the QT interval [20]. QTc changes have also been associated with specific metabolic profiles in a cohort of shift workers engaged in nonstandard working hours [21].…”
Section: Introductionmentioning
confidence: 99%
“…Pathway analysis of these metabolites revealed statistically significant abnormalities in aminoacyl-tRNA biosynthesis, sulphur, taurine and hypotaurine, citric acid cycle, thiamine, pantothenate and CoA biosynthesis, pyruvate metabolism, glutathione, glycine, serine and threonine, glyoxylate and dicarboxylate, cysteine and methionine, arginine and proline metabolism, though these did not exceed the False Discovery Rate (FDR). A prior relationship between pyroglutamic acid and QTc could not be validated (39).…”
Section: Lvsdmentioning
confidence: 99%